2002
DOI: 10.1159/000063103
|View full text |Cite
|
Sign up to set email alerts
|

Improved Iron Utilization and Reduced Erythropoietin Resistance by On-Line Hemodiafiltration

Abstract: Background: Recent investigation has shown that on-line hemodiafiltration (HDF) can reduce the amount of recombinant human erythropoietin (rhEPO) deemed necessary to reach the target hematocrit. The aim of this study was to analyze the potential effect of on-line HDF on rhEPO resistance in relation to iron utilization and anemia-related parameters, when compared to conventional hemodialysis (HD). Methods: Ninety-two chronic uremic patients were treated with conventional HD and then shifted to on-line HDF. Meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
36
2
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 14 publications
5
36
2
1
Order By: Relevance
“…For each subject, the quartile of erythropoietin response was plotted by the increase in Epoetin alfa dose at randomization (denominator of the response measure) on the horizontal axis, and hematocrit response (numerator of the response measure, which was the hematocrit slope derived from a simple linear regression of study week on hematocrit) on the vertical axis. ocrit values assessed at one point in time, including current Epoetin alfa dose (20), a ratio of Epoetin alfa dose to body weight (21), Epoetin alfa dose within levels of achieved hematocrit (19), current hematocrit (18), and average hematocrit over a specific time period (22).…”
Section: Discussionmentioning
confidence: 99%
“…For each subject, the quartile of erythropoietin response was plotted by the increase in Epoetin alfa dose at randomization (denominator of the response measure) on the horizontal axis, and hematocrit response (numerator of the response measure, which was the hematocrit slope derived from a simple linear regression of study week on hematocrit) on the vertical axis. ocrit values assessed at one point in time, including current Epoetin alfa dose (20), a ratio of Epoetin alfa dose to body weight (21), Epoetin alfa dose within levels of achieved hematocrit (19), current hematocrit (18), and average hematocrit over a specific time period (22).…”
Section: Discussionmentioning
confidence: 99%
“…Compared to standard dialysis, OL-HDF has been shown to improve the anemic status of CKD patients by significantly increasing Hb to target levels at reduced maintenance doses of EPO [26]. Two further studies showed that when patients are switched from conventional HD to OL-HDF, significantly higher hematocrit (Hct) and Hb levels were reached with the OL-HDF treatment modality [27,28 ](table 1). Attainment of higher Hct and Hb levels with more efficient dialysis therapies (HF membranes and convective therapies) has been attributed to the elimination of larger uremic retention substances that impair erythropoiesis [21,26].…”
Section: Impact Of Dialysis On Bone Marrow Erythropoiesismentioning
confidence: 99%
“…Switching patients from conventional HD to OL-HDF was associated with a reduction in EPO dose to reach a higher mean Hct level [27,28]. In a study in which patients on conventional HDF were changed to OL-HDF, an EPO dose reduction of 16% EPO was observed after the switch to OL-HDF, with significant increase in Hb and Hct levels during the OL-HDF period [26].…”
Section: Dialysis Strategies That Affect Anemia Therapymentioning
confidence: 99%
“…По данным C. Lin с соавт. и F. Maduell с соавт., достоверное по-вышение уровня гематокрита при значимом сниже-нии дозы эритропоэтина отмечалось после перево-да пациентов с СТГД на ОЛ-ГДФ [27,28].…”
Section: снижение потребности в медикаментах -лечение анемииunclassified